Post‐cardiac arrest level of free‐plasma DNA and DNA‐histone complexes. Issue 5 (23rd March 2017) - Jeppesen, A. N.; Hvas, A.‐M.; Grejs, A. M.; Duez, C. H. V.; Sorensen, B. S.; Kirkegaard, H.
Abstract : Background: Plasma DNA‐histone complexes and total free‐plasma DNA have the potential to quantify the ischaemia‐reperfusion damages occurring after cardiac arrest. Furthermore, DNA‐histone complexes may have the potential of being a target for future treatment. The aim was to examine if plasma DNA‐histone complexes and the levels of total free‐plasma DNA were elevated in post‐cardiac arrest patients compared with healthy individuals, and to examine if these biomarkers were capable of predicting mortality. Methods: We included 42 comatose out‐of‐hospital cardiac arrest patients and collected blood samples after 22, 46 and 70 h. Samples for DNA‐histone complexes were quantified by Cell Death Detection ELISA plus . The total free‐plasma DNA analyses were quantified with qPCR by analysing the Beta‐2 microglobulin gene. The control group comprised 40 healthy individuals. Results: We found no difference in the level of DNA‐histone complexes between the 22‐h sample and healthy individuals ( P = 0.10). In the 46‐h sample, there was an increased level of DNA‐histone complexes in non‐survivors compared with survivors 30 days after the cardiac arrest ( P < 0.01) and the area under the ROC curve was 0.78 (95% confidence interval: 0.59;0.96). The level of total free‐plasma DNA was increased in the 22‐h sample compared with healthy individuals ( P < 0.001) but no significant difference was found between non‐survivors and survivors 30 days after the cardiac arrest (all P ≥ 0.06). Conclusion: An increased level of DNA‐histone complexes was associated with increased mortality and that the level of total free‐plasma DNA was elevated post‐cardiac arrest.